Herbal poisoning in children, basic aspects (Revista Venezolana de Salud Pública, 2018)
Folk use of herbs and plants reputed as medicinal plants can cause adverse effects in the pediatric population, particularly newborns and infants younger with an underlying respiratory or digestive disease. Administration excessive and / or prolonged doses of a decoction in a patient previously ill, may explains herbs poisoning. Additionally, medical knowledge about herbal medicine is poor and patient’s family does not provide information about administration of these products. These circumstances could justify having basic information that allows to clinician to optimize diagnosis and treatment of plants poisoning and developing primary prevention programs.
Keywords: Herbs; folk use; poisoning; children; knowledge; diagnosis; treatment; primary prevention